Polyelectrolyte based sensors as key to achieve quantitative electronic tongues: Detection of triclosan on aqueous environmental matrices - Magro, Cátia (2020)
This work was supported by the Project “Development of Nanostructures for Detection of Triclosan Traces on Aquatic Environments” (PTDC/FIS-NAN/0909/2014). The Center for Environmental and Sustainability Research CENSE and Centre of Physics and Technological Research CEFITEC,which is ﬁnanced bynational funds from FCT/MEC (UID/AMB/04085/2019 and UID/FIS/00068/2019). This research was anchored by the RESOLUTION LAB, an infrastructure at NOVA School of Science and Technology. J. Pereira-da-Silva and P. Zagalo acknowledge their fellowships PD/BD/142768/2018, PD/BD/142767/2018 from RABBIT Doctoral Program, respectively. C. Magro acknowledges to Fundação para a Ciência e a Tecnologia for her PhD fellowship (SFRH/BD/114674/2016).